Stewardship : collaborative decentred governance and inquiring systems - Hubbard, Ruth, 1942-; Paquet, Gilles; Wilson, Christopher, 1953- (Ottawa, Canada : University of Ottawa Press, 2022)
"This first volume in the Collaborative Decentred Metagovernance Series scopes: what is meant by collaborative decentred metagovernance and stewardship; how this new problematique has emerged; on what assumptions and key concepts it is built; the central role played by inquiring systems in public policy; and how it can be used to throw some light on wicked policy problems in policy domains like health, productivity, and innovation, as well as on persistent and perplexing issues like the need to strike a new balance in conflicts with Aboriginal communities over such things as the illegal tobacco trade and self-governance. This book explains how collaborative decentred metagovernance combines forms and styles of governance being experimented with in the private, public and voluntary sectors, to ensure effective coordination when no one can legitimately lay claim to being in charge because power, resources and information are widely distributed into many hands, and governance must, of necessity, be decentred and collaborative."--
Frontmatter -- Table of Contents -- Introduction -- Chapter 1 Foundations -- Chapter 2 Inquiring Systems -- Chapter 3 Scheming Virtuously -- Chapter 4 The New Frontier -- Chapter 5 Metagovernance Review -- Conclusion -- References
Reprint. Originally published: Ottawa : Invenire Books, 2012.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on March 07, 2025).
eBooks on EBSCOhost
Keywords: Public administration -- Philosophy; Decentralization in government; Administrative agencies -- Philosophy; Social learning; Inquiry-based learning; Administration publique (Science) -- Philosophie; Administration publique -- Philosophie; Apprentissage social; Apprentissage basé sur l'enquête.; Decentralization in government; Inquiry-based learning; Public administration -- Philosophy; Social learning; Electronic books